Balance Scorecard Analysis of Increasing MSME Income During the Covid 19 Pandemic in Samosir District - Nashrudin Setiawan; Emi Wakhyuni; Abdi Setiawan (Ilomata International Journal of Social Science, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the lifeblood of the regional and national economy. In general, MSMEs in the national economy have the following roles: (1) as the main actors in economic activities, (2) the largest provider of employment, (3) important players in local economic development and community empowerment, (4) creating new markets and sources of innovation, and (5) its contribution to the balance of payments. In addition, MSMEs also have an important role, especially in the perspective of employment opportunities and sources of income for the poor, income distribution and poverty reduction, and MSMEs also play a role in rural economic development. The existence of the 2019 Coronavirus disease (Covid 19 pandemic) at the end of 2019 became an international problem, including in Indonesia. The COVID-19 pandemic has had economic, social, and and politics in almost all countries, including Indonesia. The economic impact of the COVID-19 pandemic has also been felt by the MSME sector in Samosir Regency. The impact caused by this pandemic includes 5 aspects, namely 1) Sales aspects. The average decline in MSME sales is 61%, 2) Aspects of operating profit. The average decrease in operating profit is 62%, 3) Capital aspect. The number of MSMEs experiencing capital problems increased to 71.4%, 4) Aspects of the number of employees. In this aspect, MSMEs reduced the number of employees by 22%, and 5) Aspects of the ability to pay bank installments. Almost all MSME actors (especially micro-enterprises) experience problems in carrying out their obligations to banks. This study also found that MSME actors in Samosir Regency had implemented an online sales strategy, although not all. The number of MSMEs that carry out online strategies has increased during the Covid 19. The survival ability of MSMEs that sell online is stronger than MSMEs that only sell offline.